Significant Loss of ACL Graft Force With Tibial-Sided Soft Tissue Interference Screw Fixation Over 24 Hours: A Biomechanical Study. Issue 5 (4th May 2020) - Kruppa, Philipp; Flies, Anne; Wulsten, Dag; Collette, Robert; Duda, Georg N.; Schaser, Klaus-Dieter; Becker, Roland; Kopf, Sebastian
Background: Tibial-sided graft fixation is thought to be critical for the success of anterior cruciate ligament (ACL) reconstruction. Nevertheless, little is known about the graft force after fixation during the first 24 hours after surgery or the influence of screw diameter and length during this time. Purpose: To investigate the force, over the course of 24 hours, in soft tissue grafts secured with a tibial interference screw and to evaluate the effect of different screw diameters (7, 8, and 9 mm) and lengths (25 and 30 mm) on the force in these grafts. Study Design: Controlled laboratory study. Methods: Quadruple-strand flexor tendon grafts were fixed with bioabsorbable interference screws in 60 porcine tibiae. Grafts were pretensioned at 80 N over 10 minutes, and screws were inserted outside-in while a preload force of 80 N was applied. Different screw lengths (25 and 30 mm) and diameters (7, 8, and 9 mm), resulting in 6 groups with 10 specimens each, were tested. After release of the preload, graft force was recorded over 24 hours. Results: A significant decrease in graft force progressed in all groups over the 24-hour period. In total, a median loss of 75 N (IQR, 68-79 N) compared with the initial loading force was observed. Compared with the loading force of 80 N, this corresponded to a median loss of 91%. No significant differences in the remaining graft force could be found among the 6 different screw length and diameter groups after 10 minutes, 100 minutes, or 24 hours. Conclusion: Graft force in soft tissue grafts secured with a tibial interference screw decreased substantially over the first 24 hours after fixation. Neither the screw diameter nor the screw length affected the decrease in graft force. This raises substantial questions regarding the remaining fixation strength in vivo. Clinical Relevance: It should not be expected that ACL reconstruction can mechanically restabilize an injured knee as would an intact ACL. Reconstructed knees should be protected from mechanical overload in the early postoperative period.